Endogamous Marriage of Prophet's Descendants on the Perspective of Sociology of Islamic Law - Fauzan; M. Harir Muzakki; Imam Syafi'i; Bustomi; Abdul Qodir Zaelani (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2023)
This study aims to comprehensively describe the endogamous marriages of the Prophet Muhammad's descendants from the perspective of the sociology of Islamic law. The marriage mainly occurs in syarīfah (the female descendants); they are required to marry the prospectives from ḥabīb (male descendants) groups only. Endogamous marriage will be explored holistically by clarifying the reciprocal relationship between social change and Islamic law among syarīfah. This field research examines the enactment of the law in social life. It used a sociological Islamic law approach to reveal the facts about endogamous marriage in Bangil, East Java, Indonesia, because many of the Prophet's descendants live there. Data collection techniques were interviews and literature search, while the analysis technique used is Miles and Hubermen's analytical procedure. After conducting in-depth research, a conclusion was found that endogamous marriage among syarīfah in Bangil is a form of obedience to customs passed down across generations since their ancestors, namely the tradition of marrying someone of equal lineage. Endogamous marriages have been maintained to this day due to religious teachings, the spirit of protecting the Prophet's family, and the social conditions of those who support its preservation.